Process of Transformation of ’I’ into ’We’: Critical Study of Communication Behaviour of Spectator-Performer Relationship in Theatre - Swami, Yogita (International Journal of Psychosocial Rehabilitation, 2019)
The interrelationship of the actor and the audience has always affected the theater activity in terms of space, action, structure, and so on. Many times it has motivated us to evolve new methods for better communication with a definite object. The circle of communication for the transfer of the dramatic material from the sender—the author of the material—to the receiver—the audience—and its feedback to the author again through the reactions and criticism has always been a very complicated journey with several layers of human nature. The process of encoding and decoding from both ends, that is, the sender at one end and the receiver at the other end, involves many levels of interpretation of the text during this transfer, which ultimately proves to be a deciding factor for the assessment of the actor-audience relationship during ‘those’ moments of happening in the dramatically charged space. The interaction of these groups—the sender and the receiver, or the groups of actors and the spectators—provides a more creative ground when they seem to be standing at the same level of experience and understanding during the course of their interaction.